(untitled) (Experimental biology, 2023)
Based on the collected material in the period 2021-2022 from small reservoirs of the Ile – Balkhash basin (Almaty region) there were 19 species of fish, which belong to 4 orders, 8 families. The species diversity of the studied reservoirs consists of native (25%) and alien (75%) fish species. The greatest species diversity was observed in the pond of the Kapshagai spawning farm (11 species), the least species diversity was noted in the Lepka river (1 species). As a result of the cluster analysis of the similarity of species diversity, the greatest similarity was found between the rivers: Maly Charyn – Kainazar-Issyk – River No. 3 (72%). The similarity of species diversity between the Talgar – Issyk rivers was 54.5%. The similarity of the ichthyofauna of the Lepka River with the ichthyofauna of the Kapshagai spawning farm was 16.6%. Nitrate pollution is noted in all the small rivers studied. Of the native fish species, the spotted sponge Triplophysa strauchii dominates in number and distribution (47.67%). Small species are the Balkhash minnow (0.06%) and the Tibetan char (0.02%). Thus, the data obtained indicate a significant reduction in the ranges of native fish. Of the alien fish species, the Amur chebachok, Chinese gorchak and river abbotina dominated, which have no economic value, and also pose a threat to the preservation of the native ichthyofauna.